SNESS - An Expert System Shell - Singh, Pratul (1994)
Looking at the prevailing trend, an attempt has been made in this thesis to develop a shell on PC, using C++ language. C++ language is an extension of C language and it retains the efficiency of C and is compatible with existing C programs. In the present work we have emphasized on the core of an expert system shell which consists of a facility to input knowledge and create a knowledge base and an inference engine that operates on the knowledge base to develop the desired system.